COVID-19 vaccine uptake and hesitancy among HIV-infected men who have sex with men in mainland China: a cross-sectional survey. Issue 12 (2nd December 2021) - Zheng, Weiran; Sun, Yinghui; Li, Hui; Zhao, Heping; Zhan, Yuewei; Gao, Yanxiao; Hu, Yuqing; Li, Peiyang; Lin, Yi-Fan; Chen, Hui; Meng, Huicui; Yang, Chongguang; et al.
ABSTRACT: Background: Men who have sex with men (MSM), a population bearing the greatest HIV burden in many countries, may also be vulnerable to COVID-19. COVID-19 vaccines are essential to containing the pandemic. However, vaccine hesitancy may compromise vaccine coverage. We aimed to understand the uptake of COVID-19 vaccine and factors associated with COVID-19 vaccine hesitancy among HIV-infected MSM in mainland China. Methods: A cross-sectional online survey among HIV-infected MSM was conducted between 13 and 21 February 2021 in mainland China. Variables including demographics, mental health status, HIV characteristics, and knowledge of and attitudes toward COVID-19 pandemic and COVID-19 vaccine were collected. Chi-square tests and multivariable logistic regression were used to analyze factors associated with COVID-19 vaccine hesitancy. Results: A total of 1295 participants were included. The median age was 29.3 years (interquartile range [IQR] 25.2–34.0 years). The uptake of COVID-19 vaccine was 8.7%. Two main reasons for receiving vaccines were "regarded vaccination as self-health protection" (67.3%) and "trust in domestic medical technology" (67.3%). Among participants who did not initiate vaccination, concern about side effects (46.4%) and disclosure of HIV infection (38.6%) were top two reasons, and 47.2% had higher vaccine hesitancy. Men who had with high antiretroviral therapy (ART) adherence (adjusted odds ratio [aOR] 0.53, 95% confidence interval [CI] 0.35–0.80), often (0.26, 0.17–0.40) or sometimes (0.46, 0.31–0.67) paid attention to information about the COVID-19 vaccine, preferred domestic vaccines (0.37, 0.24–0.59), thought the pandemic had moderate (0.58, 0.38–0.90) and moderately severe or severe impact (0.54, 0.38–0.78) on immunity, who were waiting for vaccination programs organized at workplace (0.60, 0.44–0.81) and who were unaware of where to get COVID-19 vaccine (0.61, 0.45–0.82) had lower degree of COVID-19 vaccine hesitancy. Men who were concerned about the efficacy (1.72, 1.16–2.54) and side effects (2.44, 1.78–3.35) had higher degree of COVID-19 vaccine hesitancy. Conclusion: COVID-19 vaccine uptake among HIV-infected MSM is still suboptimal. Understanding influencing factors of vaccine hesitancy among this group and making tailored measures to alleviate hesitancy would help improve the coverage of COVID-19 vaccination in this population.